THE IMPACT OF MACHINE TRANSLATION ON ENHANCING STUDENTS’ TRANSLATION SKILLS IN WRITING - Putri, Citra Anggia; Sibarani, Berlin (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This study explores how machine translation (MT) tools, particularly Google Translate, can be utilized to improve translation skills in writing among English Literature students. The participants of this research were ten English literature students. Employing a qualitative research with case study as the research design. The data were collected using in-depth interviews followed by observation and translation tasks. As digital tools become increasingly integrated into language learning, it is important to understand both the pedagogical benefits and limitations of MT in academic settings. This case study investigates how students use MT in translating literary and academic texts, how they evaluate the accuracy of MT outputs, and how they engage in post-editing to enhance their linguistic awareness and critical thinking. The findings are expected to provide practical insights for incorporating MT tools into translation teaching strategies while fostering students' autonomy and accuracy in translation.